Analisis Swot Sebagai Strategi Dalam Meningkatkan Keunggulan Bersaing Baznas Kota Palembang - Esa Rahmahesa; Iceu Sri Gustiana; Safitri Asrol (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This research is entitled SWOT analysis as a strategy to increase the competitive advantage of BAZNAS Palembang City. The method used in this research is a qualitative or field method, namely collecting primary data by describing the condition of the object being studied in the field, then the problems that arise will be reviewed and analyzed in depth based on factual and accurate data using data collection techniques in the form of observation, interviews. and documentation. Based on the research results, BAZNAS Palembang City has implemented a strategy for managing zakat funds well and professionally. The SWOT analysis shows that the national zakat management institution has strengths in terms of effective and efficient zakat collection, but also has weaknesses in transparency and accountability. The opportunities that exist for national zakat management institutions are increasing cooperation with related parties and utilizing technology, while the threats faced are competition with other zakat management institutions and changes in regulations.